Antiangiogenic therapy in hematologic malignancies - Möhler, Thomas; Hillengaß, Jens; Goldschmidt, Hartmut; Ho, Anthony Dick (Current pharmaceutical design, 2004)
Angiogenesis is defined as the formation of new capillaries from prexisting blood vessels and plays an important role in the progression of solid tumors an...
Gesehen am 03.12.2021